(En)Gendering Difference: A For(u)m for Possibilities (LEARNing Landscapes, 2011)
This inquiry observes how cultural collaborations can create for(u)ms—forms representing narrative activity; for-"ums" for reflective pauses; and forums for discussion— to critically address and provide spaces for playing in and with differences in ability, race, gender, and ethnicity. Using the project gender/TROUBLING as template, it theorizes a performative model for learning to explore the possibilities for engendering diversity and for building responsive, creative, and inclusive teaching/learning practices.
Keywords: inquiry; cultural collaboration; for(u)m; narrative; gender; ethnicity; race; ability; engendering; practice; teaching; learning